THE EFFECT OF SALES GROWTH, CURRENT RATIO AND ROE ON PROFIT CHANGES - Trisandi Eka Putri; Wellcy Zahratunijah Az-Zahra (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2024)
In this era of globalization there are many developments that have provided major changes to various fields, especially in the economic field. As for the purpose of this study, it aims to determine the effect of sales growth, current ratio and ROE on profit changes in food & beverages sub-sector companies that have been listed on the Malaysian stock exchange (2018-2021 period). This study uses financial statement data from 24 companies with a span of 4 years from 2018-2021 using a purpose sampling technique. The analytical technique used in this study uses multiple regression analysis assisted by SPSS. The results of this study indicate that the sales growth variable has a positive effect on changes in profit, while current ratio and ROE has no effect on changes in profit. As for the simultaneous results that the sales growth, current ratio and ROE have an effect on changes in profit.